(untitled) - Energy Sector Management Assistance Programe (ESMAP) ([Ha Noi], 2010)
This report propose a vision, a sector framework and the sketch of a coordinated implementation roadmap for gas in Vietnam.
Keywords: Khí thiên nhiên,Natural gas,Sự phát triển của ngành năng lượng,Energy development; Luật pháp vá sự ban hành các quy định,law and legislation; Việt Nam,Việt Nam,Việt Nam,Việt Nam